Corneal biomechanical stiffness and histopathological changes after in vivo repeated accelerated corneal cross-linking in cat eyes. (February 2023) - Zhang, Xiaoyu; Sun, Ling; Chen, Lingfeng; Zhang, Chaoqin; Xian, Yiyong; Aruma, Aruma; Wei, Ruoyan; Shen, Yang; Chen, Weiyi; Zhou, Xingtao
Abstract: Corneal cross-linking (CXL) has been proved efficiency for treating progressive keratoconus and other corneal ectasia diseases by stabilizing corneal geometry and biomechanics. However, the necessity of repeated CXL treatment in patients is unknown. This study aimed to investigate corneal biomechanical stiffness and change in corneal histopathological characteristics after repeated accelerated CXL (A-CXL) in cat eyes. A-CXL was performed with 0.1% riboflavin applied for 10 min, followed by ultraviolet A irradiation at 30 mW/cm 2 for 3 min at 365 nm in 15 domestic cats. Corneas (n = 30) were divided into three groups: one-time accelerated corneal cross-linking (A-CXL*1 group), repeated accelerated corneal cross-linking (A-CXL*2 group), and an untreated control group. In A-CXL*2 group, A-CXL was repeated at 1-month intervals. In vivo ocular examinations were performed pre- and postoperatively. Biomechanical analysis was performed using a biotester biaxial testing system. We used the Mooney–Rivlin strain-energy function to describe corneal material properties. No infection in any case after A-CXL was observed. Biomechanical tests showed that the stress-strain curves of the two A-CXL groups were significantly different from those of the control group (P < 0.01), whereas stress-strain curve of the A-CXL*2 group was similar to that of the A-CXL*1 group (P > 0.05). Delayed epithelial healing and haze were observed 1 month after surgery. Stromal demarcation line depth measured with anterior spectral-domain optical coherence tomography was 187.6 ± 20.4 and 197.1 ± 11.5 μm for the A-CXL*1 and A-CXL*2 groups, respectively (P > 0.05). These results show that A-CXL can increase corneal biomechanics in cat eyes. The biomechanical enhancement of cat corneas treated with repeated A-CXL at 1-month intervals was similar to that of performing a one-time A-CXL. Repeated cross-linking procedures at short intervals may increase the risk of adverse reactions, and more caution should be taken in clinical applications. Highlights: Repeated A-CXL does not produce enhancement of biomechanical effect in comparing to one-time A-CXL at 1-month intervals.